2017
DOI: 10.1159/000485398
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Practices in Pediatric Dialysis Patients Across Europe. A European Pediatric Dialysis Working Group and European Society for Pediatric Nephrology Dialysis Working Group Study

Abstract: Background: Data on the immunization practices in pediatric chronic kidney disease (CKD) patients are scarce. The purpose of this study was to evaluate current vaccination practices for children on dialysis across European pediatric nephrology centers. Methods: A total of 18 tertiary pediatric nephrology centers from 12 European countries were included in the study. The data on universal national immunization programs and immunization practices for children with chronic disease or risk were recorded from Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
4
0
5
Order By: Relevance
“…BCG is included in the national schedule for some countries for all children and in other countries, only in children at risk of TB infection. In some countries, CKD is considered a risk factor for TB disease in itself and it is therefore recommended for all these children if not previously administered [39][40][41]. A recent survey in 18 tertiary paediatric nephrology centres from 12 European countries showed that BCG was recommended as part of the national schedule in five countries, recommended in CKD in three countries and had no specific recommendation in the remaining four countries [39].…”
Section: Bacillus Calmette-guérin Vaccine Bcg Development and Immunismentioning
confidence: 99%
See 1 more Smart Citation
“…BCG is included in the national schedule for some countries for all children and in other countries, only in children at risk of TB infection. In some countries, CKD is considered a risk factor for TB disease in itself and it is therefore recommended for all these children if not previously administered [39][40][41]. A recent survey in 18 tertiary paediatric nephrology centres from 12 European countries showed that BCG was recommended as part of the national schedule in five countries, recommended in CKD in three countries and had no specific recommendation in the remaining four countries [39].…”
Section: Bacillus Calmette-guérin Vaccine Bcg Development and Immunismentioning
confidence: 99%
“…BCG immunisation for children with CKD or undergoing kidney transplantation has previously been advocated in some low incidence settings [39]. However, some caution for the use has been expressed, in particular for those children who are receiving immunosuppressive therapy or are known to have an underlying immunodeficiency.…”
Section: Bcg Riskmentioning
confidence: 99%
“…Kronik böbrek yetersizliği (KBY) hastalarında enfeksiyonlar en sık ölüm nedenlerindendir (3). İmmünsüpresif ilaç tedavileri, üremik toksinler, diyaliz tedavisi, malnütrisyon ve aşı sonrası düşük antikor yanıtı KBY hastalarının enfeksiyonlara daha duyarlı olmasının başlıca nedenleridir (4)(5)(6). Bu bakımdan KBY hastalarında ulusal aşı takvimine ek olarak aşı takviminde olmayan aşıların da tamamlanması önerilmektedir.…”
Section: Introductionunclassified
“…For instance, repeated booster doses of pneumococcal vaccine were found to reduce infection rates among dialysis patients within 2 years, whereas doubling the dosage of hepatitis B vaccine has seen improvements in immunization response against HBV infection [6][7][8]. Vaccination of CKD patients is far advanced in the developed countries with only minor differences in practice and attainment of recommended targets among them [9]. However, the same cannot be said for nephrology practice in Nigeria and many other countries in Sub-Saharan Africa as their dismal performance in this aspect of CKD care is mirrored by a lack of data or research on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, repeated booster doses of pneumococcal vaccine were found to reduce infection rates among dialysis patients within 2 years, whereas doubling the dosage of hepatitis B vaccine has seen improvements in immunization response against HBV infection [ 6 8 ]. Vaccination of CKD patients is far advanced in the developed countries with only minor differences in practice and attainment of recommended targets among them [ 9 ].…”
Section: Introductionmentioning
confidence: 99%